Effect of water film on the nano-scratching process of 4H-SiC under the constant load. (November 2022) - Zhou, Yuqi; Huang, Yuhua; Li, Jinming; Zhu, Fulong
Abstract: The effects of water film and scratching load on tribological properties are investigated by molecular dynamics simulation. Water film is found to reduce the average friction coefficient and enhance heat dissipation of scratching process. The long dislocations in 4H‐SiC are related to the formation of continuous and stable Si-Si bonds, and the water film can inhibit the formation of dislocations by affecting Si-Si bonds. Scratching in water-wetted environments has a positive effect on improving surface quality and reducing sub-surface damage, but has a negative impact on the material removal rate. The effect of increasing load is opposite to that of adding water. These results confirm the lubrication effect of water film in global planarization process from a theoretical perspective. Graphical Abstract: ga1 Highlights: The nano-scratching model of 4H‐SiC in water-wetted environment is established. The lubrication of water can reduce the tangential force and friction coefficient. The water film can enhance heat dissipation and reduce chip accumulation. The water film can reduce phase transition and surface damage after scratching. The water film can inhibit the formation of dislocations by affecting Si-Si bonds.